Design methodology and productivity improvement in high speed VLSI circuits - Hossain, KM Mozammel, author; Chen, Thomas W., advisor; Malaiya, Yashwant, committee member; Pasricha, Sudeep, committee member; Pezeshki, Ali, committee member (Colorado State University. Libraries, 2017)
To view the abstract, please see the full text of the document.